Regulation of DNA Replication Initiation by Chromosome Structure - Magnan, David (J Bacteriol, 2015)
Recent advancements in fluorescence imaging have shown that the bacterial nucleoid is surprisingly dynamic in terms of both behavior (movement and organization) and structure (density and supercoiling). Links between chromosome structure and replication initiation have been made in a number of species, and it is universally accepted that favorable chromosome structure is required for initiation in all cells. However, almost nothing is known about whether cells use changes in chromosome structure as a regulatory mechanism for initiation. Such changes could occur during natural cell cycle or growth phase transitions, or they could be manufactured through genetic switches of topoisomerase and nucleoid structure genes. In this review, we explore the relationship between chromosome structure and replication initiation and highlight recent work implicating structure as a regulatory mechanism. A three-component origin activation model is proposed in which thermal and topological structural elements are balanced with trans-acting control elements (DnaA) to allow efficient initiation control under a variety of nutritional and environmental conditions. Selective imbalances in these components allow cells to block replication in response to cell cycle impasse, override once-per-cell-cycle programming during growth phase transitions, and promote reinitiation when replication forks fail to complete.